Infection of Salmonella sp. in Gastrointestinal Tract of Magelang Duck Reared Intensively and Semi-intensively - Monica Sonia Indri Pradipta (LPPM Perjuangan University of Tasikmalaya, 2020)
The digestive tract is the main health center of an animal. When the balance of microflora in the digestive tract is disturbed, it becomes susceptible to be infected with pathogenic bacteria. This research was conducted to examine the effect of intensive and semi-intensive type of maintenance on the amount of Salmonella sp. on the profile of the Magelang duck digestive tract. Total contamination of Salmonella sp. and the total bacteria in the Magelang duck intestine were tested according to SNI 2897-2008. This research is a step that can be used to help farmer deal with the problem of pathogenic bacterial infections in a pattern of maintenance that is suspected to have high Salmonella contamination. Based on research that has been done, it can be concluded that neither the maintenance of intensive or semi-intensive ducks does not indicate the presence of Salmonella sp. From the two maintenance systems, it is obtained that the semi-intensive maintenance of Magelang ducks shows the number of digestive tract microflora which is higher than intensive maintenance.Keywords: Â Magelang duck, Salmonella sp.